Relative importance index (RII) in ranking of quality factors on industrialised building system (IBS) projects in Malaysia - Azman N.S.; Ramli M.Z.; Razman R.; Zawawi M.H.; Ismail I.N.; Isa M.R. (American Institute of Physics Inc., 2023)
The purpose of this paper is to identify and determine the factors affecting the quality management of construction projects by using Industrialised Building System (IBS) and analyze the factors using Relative Importance Index (RII) method. In Malaysia, the used of the Industrialised Building System (IBS) in the construction industry has been rise as it gives many benefits to the project. However, without a decent quality management of the IBS product, it might give a bad perspective from the customers who are the contractors or consultants. From the previous literatures, hundred and nine (109) factors affecting the quality management of construction project that using Industrialised Building System (IBS) were identified and. In this study, the method used for data collection is by distribution of questionnaire. Most significance factors affecting the quality in construction were identified which is proper production equipment and technology with highest value of RII = 0.684. This study has important contribution to help project players of construction industry to ensure and maintain the good quality in construction while using Industrialised Building System (IBS) in future construction. 2019 Author(s).